Topology and geometry of biopolymers : AMS Special Session on Topology of Biopolymers, April 21-22, 2018, Northeastern University, Boston, Massachusetts - Flapan, Erica, 1956-; Wong, Helen, 1978- (Contemporary mathematics (American Mathematical Society), 2020)
This book contains the proceedings of the AMS Special Session on Topology of Biopolymers, held from April 21-22, 2018, at Northeastern University, Boston, MA. The papers cover recent results on the topology and geometry of DNA and protein knotting using techniques from knot theory, spatial graph theory, differential geometry, molecular simulations, and laboratory experimentation. They include current work on the following topics: the density and supercoiling of DNA minicircles; the dependence of DNA geometry on its amino acid sequence; random models of DNA knotting; topological models of DNA r.